Risk factors associated to infection and mortality by oxacillin-resistant Staphylococcus aureus (ORSA) in a hospital of reference for infecto-contagious diseases de Goiânia-GO, Brazil - Sant´Anna Diniz e Moura, Jordanna; da Silva Souza, Paula Danielli; Toledo Menezes, Rodrigo; Salgado, Cláudia Maria; Leite Pineli Simões, Luciana; Rodrigues do Carmo Filho, José (O Mundo da Saúde, 2011)
Staphylococcus aureus are important agents of hospital infections, especially bloodstream primary infections. The objectives of this study were to identify risk factors for infection by ORSA and risk factors associated to ORSA mortality, and to describe the profile of susceptibility to antimicrobiotic substances. We did a case control study with 44 medical registers of patients diagnosed with hospital infection by ORSA from April 2005 to July 2008. Independent risk factors for infection and mortality were defined after univariate and multivariate analysis. Independent risk factors for infection by ORSA were the use of antibiotics in the last 15 days preceding the isolation of ORSA and the use of total parenteral nutrition. The independent risk factor for death was the use of mechanical ventilation. The most frequent places for ORSA isolation were the blood and secretions. The more frequent base diseases of patients infected by SARO were AIDS, bloodstream infection and pneumonia.